Role of the Oxytocin Receptor Expressed in the Rostral Medullary Raphe in Thermoregulation During Cold Conditions - Kasahara, Yoshiyuki; Tateishi, Yuko; Hiraoka, Yuichi; Otsuka, Ayano; Mizukami, Hiroaki; Ozawa, Keiya; Sato, Keisuke; Hidema, Shizu; Nishimori, Katsuhiko (Frontiers in Endocrinology, 2015)
Recent papers have reported that oxytocin (Oxt) and the oxytocin receptor (Oxtr) may be involved in the regulation of food intake in mammals. We therefore suspected the Oxt/Oxtr system to be involved in energy homeostasis. In previous studies, we found a tendency toward obesity in Oxtr-deficient mice, as well as impaired thermoregulation when these mice were exposed to cold conditions. In the present study, we observed the expression of Oxtr in the rostral medullary raphe (RMR), the brain region known to control thermogenesis in brown adipose tissue. Through immunohistochemistry, we detected neurons expressing Oxtr and c-Fos in the RMR of mice exposed to cold conditions. Up to 40% of Oxtr-positive neurons in RMR were classified as glutamatergic neurons, as shown by immunostaining using anti-VGLUT3 antibody. In addition, mice with exclusive expression of Oxtr in the RMR were generated by injecting an AAV-Oxtr vector into the RMR region of Oxtr-deficient mice. We confirmed the recovery of thermoregulatory ability in the manipulated mice during exposure to cold conditions. Moreover, mice with RMR-specific expression of Oxtr lost the typical morphological change in brown adipose tissue observed in Oxtr-deficient mice. Additionally, increased expression of the β3-adrenergic receptor gene, Adrb3 was observed in brown adipose tissue. These results are the first to show the critical role of RMR Oxtr expression in thermoregulation during cold conditions.